A Global Research Trend on Leadership in Sport: A Bibliometric Analysis - Ling Gan, Jen; Mohd Yusof, Halimah (International Journal of Psychosocial Rehabilitation, 2020)
The contribution of leadership in the sports industry has been slowly recognized by the scholars. Effective leadership in sport is believed to be able to enhance the performance of sport teams, as well as the performance of sport organizations. However, to date, there is no bibliometric analysis conducted on sport leadership. Hence, a bibliometric analysis is necessary to evaluate the global research growth to retrieve and analyze the publication on sport leadership in order to enhance the performance of sport teams. The bibliometric analysis is used to search the database of Scopus from the oldest publication in 1956 to the recent publication in 2019. This study used VOS Viewer 1.6.11 to analyze and visualize the global research trend on sport leadership in analyzing the bibliographic data. The objectives were to evaluate the output of publications, co-authorship, leading countries, and cooccurrences of author keywords. This study retrieved 945 journal articles from the Scopus database from 1960 to 2019. The publication’s trend revealed that the number of publications has been increasing rapidly since 2009. The leading countries in ethical leadership research are the United States and the United Kingdom. Among the author keywords, ‘coach’ has the most links with sport leadership, which indicated the importance of sport leadership among coaches. Recommendations were discussed in this paper for future researchers.